2015
DOI: 10.1093/nar/gkv332
|View full text |Cite
|
Sign up to set email alerts
|

JPred4: a protein secondary structure prediction server

Abstract: JPred4 (http://www.compbio.dundee.ac.uk/jpred4) is the latest version of the popular JPred protein secondary structure prediction server which provides predictions by the JNet algorithm, one of the most accurate methods for secondary structure prediction. In addition to protein secondary structure, JPred also makes predictions of solvent accessibility and coiled-coil regions. The JPred service runs up to 94 000 jobs per month and has carried out over 1.5 million predictions in total for users in 179 countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,397
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,642 publications
(1,446 citation statements)
references
References 37 publications
38
1,397
1
10
Order By: Relevance
“…It is highly conserved and consists of one or two alpha helices and a transmembrane *Secondary structure predictions were made with the Jnet algorithm (Cuff & Barton, 2000) on the Jpred4 server ( (Drozdetskiy et al, 2015) Geobacter uraniireducens…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is highly conserved and consists of one or two alpha helices and a transmembrane *Secondary structure predictions were made with the Jnet algorithm (Cuff & Barton, 2000) on the Jpred4 server ( (Drozdetskiy et al, 2015) Geobacter uraniireducens…”
Section: Resultsmentioning
confidence: 99%
“…Alpha helices and beta strands were predicted with the Jnet algorithm (Cuff & Barton, 2000) on the JPred4 server (Drozdetskiy et al, 2015) and transmembrane helices were predicted with TMpred (Hofmann & Stoffel, 1993), TMHMM (Krogh et al, 2001), and HMMTOP (Tusnády & Simon, 2001). Signal peptides were identified with PSORTb v. 3.0.2 (Yu et al, 2010) and Signal P v. 4.1 (Petersen et al, 2011).…”
Section: Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Secondary structure prediction of lips221 by JPRED4 (Drozdetskiy et al 2015) suggested all SFK3309 mutations fell in loop regions and are less probable to severely disrupt overall protein structure.…”
Section: Discussionmentioning
confidence: 99%